2022
DOI: 10.1029/2022gl098003
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation Between Basal Erosion of the Lithosphere and Surface Heat Flux for Continental Plume Tracks

Abstract: While hotspot tracks beneath thin oceanic lithosphere are visible as volcanic island chains, the plume‐lithosphere interaction for thick continental or cratonic lithosphere often remains hidden due to the lack of volcanism. To identify plume tracks with missing volcanism, we characterize the amplitude and timing of surface heat flux anomalies following a plume‐lithosphere interaction using mantle convection models. Our numerical results confirm an analytical relationship in which surface heat flux increases wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 57 publications
2
20
2
Order By: Relevance
“…These examples illustrate that the thin-lithosphere channels can be created not only by rifts, such as those radiating from the Afar triple junctions, but also by other processes, such as the passage of a lithospheric plate above the plume, or simply be pre-existing areas of thinner lithosphere. Numerical modeling studies corroborate the idea that the passage of a plate over a plume can erode lithosphere and create thin-lithosphere channels (e.g., Burov & Gerya, 2014;Heyn & Conrad, 2022;Koptev et al, 2017Koptev et al, , 2018Sobolev et al, 2011).…”
Section: Evolution Of the East Africa-arabia Systemsupporting
confidence: 53%
“…These examples illustrate that the thin-lithosphere channels can be created not only by rifts, such as those radiating from the Afar triple junctions, but also by other processes, such as the passage of a lithospheric plate above the plume, or simply be pre-existing areas of thinner lithosphere. Numerical modeling studies corroborate the idea that the passage of a plate over a plume can erode lithosphere and create thin-lithosphere channels (e.g., Burov & Gerya, 2014;Heyn & Conrad, 2022;Koptev et al, 2017Koptev et al, , 2018Sobolev et al, 2011).…”
Section: Evolution Of the East Africa-arabia Systemsupporting
confidence: 53%
“…For example, we model deformation solely through a diffusion‐creep rheology, neglecting dislocation creep, Peierls creep, elasticity and brittle‐plastic deformation within the lithosphere. Incorporating a more complete description of the rheology could influence the distribution of plume material at the LAB and impact the associated lithospheric erosion and melt productivity (e.g., Burov & Gerya, 2014; Davies, 1994; Heyn & Conrad, 2022; Koptev et al., 2018); nonetheless, first‐order model predictions should remain consistent. Furthermore, we consider the upper mantle to be incompressible and ignore the effect of phase transitions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent shear‐wave splitting study, however, suggested that the plume impinging may be confined to the center of the ELIP (Li, Chen, et al., 2021). Tracing such hidden hotspot tracks thus may require finding more evidence of seismic signatures associated with plume‐related modification of continental lithosphere (Sleep, 1990), for example, reduced velocities (e.g., Stachnik et al., 2008), high attenuation (Chu et al., 2013), and thinning of the lithosphere (Heyn & Conrad, 2022) reported in similar studies worldwide.…”
Section: New Crustal Constraints and Tectonic Interpretationsmentioning
confidence: 99%